Efficacy and safety of Tanshinone capsule in Acne vulgaris: a systematic review and meta-analysis - Deng, Yutong; Feng, Ruli; Hu, Bo; Ren, Xuewen; Zhang, Fengchuan; Feng, Huishang; Wang, Xuewan; Li, Yatong; Liu, Tangyunni; Cai, Lingling; Li, Yuanwen (Frontiers in Pharmacology, 2025)
ObjectivesTo evaluate the efficacy and safety of Tanshinone capsule as a complementary therapy in managing of Acne Vulgaris.MethodsA systematic search of six databases was conducted to identify relevant randomized controlled trials (RCTs) from each database for nearly 20 years (from 1 Jan 2004, to 1 June 2024). The Cochrane Handbook was used to evaluate the risk of bias. Meta-analysis was performed using Review Manager 5.4.1, and publication bias was assessed the Stata SE 12.0 software. GRADEpro was used to assess the quality of the evidence.ResultsA total of 2,969 participants from 28 studies were included. We found that Tanshinone capsules can reduce acne recurrence rates [risk ratio (RR) 0.44, 95% confidence interval (CI): 0.34 to 0.57, p < 0.00001]; downregulate levels of necrosis factor-alpha (TNF-α) [ mean difference (MD) 0.44, −10.18, 95% CI: −13.57 to −8.04, p < 0.00001], interleukin (IL) 4 (MD -6.46, 95%CI: −7.14 to −5.77, p < 0.00001), IL-6 (MD -16.14, 95%CI: −30.10 to −2.18, p = 0.02), IL-8 (MD -4.48, 95%CI: −8.30 to −0.65, p = 0.02) and testosterone (MD -14.50, 95%CI: −17.59 to −11.40, p < 0.00001); lower Global Acne Grading System (GAGS) score (MD -4.71, 95%CI: −7.62 to −1.80, p = 0.002); decrease sebum secretion rates (MD -0.29, 95%CI: −0.49 to −0.10, p = 0.003), but the regulation of Luteinizing hormone (LH), Follicle-stimulating hormone (FSH), Estradiol (E2) is not obvious. In terms of safety, the incidence of adverse events in the experimental group was less than that in the control group (RR 0.70, 95%CI: 0.56 to 0.87, p = 0.001). The Begg test and Egger test results indicated no publication bias. Furthermore, the levels of evidence ranged from very low to moderate due to risk of bias and heterogeneity.ConclusionTanshinone capsules can relieve the symptoms of acne vulgaris, regulate inflammatory cytokines and hormone levels in patients, and reduce recurrence. However, due to the limitations of this study, more multi-center and large-sample studies are needed to confirm these conclusions.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024562320, identifier CRD42024562320.